ОСНОВНІ АСПЕКТИ ФОРМУВАННЯ ПРОФЕСІЙНОЇ МАЙСТЕРНОСТІ У МАЙБУТНІХ ВИКЛАДАЧІВ З ФІЗИЧНОГО ВИХОВАННЯ (Педагогіка вищої та середньої школи, 2007)
The increasement of students’ interest in the ultimate result of education forms the active attitude towards the process of studying. These are the main points of gaining the professional skills during the studying at the university.